2022
DOI: 10.33899/ijvs.2022.132478.2096
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic tree constructed of Salmonella enterica subspecies enterica isolated from animals and humans in Basrah and Baghdad governorates, Iraq

Abstract: The genetic relatedness of Salmonella enterica sub sp. enterica isolated from human and animal origin has more interest as its data possibly will offer an essential confirmation for the source of human infection. This study aimed to determine the genetic relationship of S. enterica subspecies enterica isolated from human and animal sources. A total of 300 samples were collected from two primary sources, human and animal, from two different regions, Baghdad and Basrah governorates. For constructing the phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In some studies, snakes have been found to have the greatest diversity of Salmonella subspecies [32]. Of all Salmonella enterica subspecies, enterica has been considered the most prevalent subspecies in reptiles [38,39]. However, we have isolated this subspecies with a low prevalence.…”
Section: Discussionmentioning
confidence: 81%
“…In some studies, snakes have been found to have the greatest diversity of Salmonella subspecies [32]. Of all Salmonella enterica subspecies, enterica has been considered the most prevalent subspecies in reptiles [38,39]. However, we have isolated this subspecies with a low prevalence.…”
Section: Discussionmentioning
confidence: 81%